The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12887-020-02095-9
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid level as an outcome predictor in pediatric patients with intussusception in the emergency department

Abstract: Background: Intussusception decreases blood flow to the bowel, and tissue hypoperfusion results in increased lactic acid levels. We aimed to determine whether lactic acid levels are associated with pediatric intussusception outcomes. Methods: The electronic medical records of our emergency department pediatric patients diagnosed with intussusception, between January 2015 and October 2018, were reviewed. An outcome was considered poor when intussusception recurred within 48 h of reduction or when surgical reduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Indeed, differences were found in the serum lactate levels and base excess, which are possible markers of organ failure, in patients assessed before and after the COVID-19 outbreak. In particular, high serum lactate levels have been associated with poor outcomes of intussusception [26]. Although air enema reduction was delayed for about 0.5 h in patients who visited during the pandemic period, the duration of illness in these patients was similar to that in patients who visited during the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, differences were found in the serum lactate levels and base excess, which are possible markers of organ failure, in patients assessed before and after the COVID-19 outbreak. In particular, high serum lactate levels have been associated with poor outcomes of intussusception [26]. Although air enema reduction was delayed for about 0.5 h in patients who visited during the pandemic period, the duration of illness in these patients was similar to that in patients who visited during the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 92%
“…The COVID-19 pandemic resulted in patient reluctance to visit the emergency department (ED) [19,20], which can delay various surgical emergencies and can worsen their clinical courses [21][22][23]. Especially in intussusception, the most common surgical emergency in young children, a delay in visiting the ED and in intervention can increase the risks of surgical reduction and poor outcomes [24][25][26][27]. Therefore, this study assessed the changes in the incidence and clinical characteristics of intussusception between the pre-pandemic and COVID-19 pandemic periods.…”
Section: Introductionmentioning
confidence: 99%
“…The result was that patients who received intravenous fluids before 30 minutes had a 12% shorter length of stay compared to patients who received intravenous fluids after 30 minutes (HR 1.14; 95% CI, 1.02-1.27). 4,8,9 This study has several limitations that might have an influence on the results of this study which showed a negative correlation between lactic acid levels and the incidence of perforated appendicitis. This study had a sample size that was less than the minimum number of samples because the study was conducted in a type A general hospital (main referral hospital) where cases of acute appendicitis were rare.…”
Section: Discussionmentioning
confidence: 88%
“…Intussusception is a common cause of bowel resection in infants and young children [ 7 , 8 ]. It is well-established that prompt identification and management are crucial for reducing the incidence of intestinal necrosis resulting from intussusception.…”
Section: Discussionmentioning
confidence: 99%